Effect of green-lipped mussel (Perna canaliculus) supplementation on faecal microbiota, body composition and iron status markers in overweight and obese postmenopausal women: a randomised, double-blind, placebo-controlled trial. - Abshirini M; Coad J; Wolber FM; von Hurst P; Miller MR; Tian HS; Kruger MC (Cambridge University Press, 2023)
The present study aimed to determine the effect of whole meat GSM powder on gut microbiota abundance, body composition and iron status markers in healthy overweight or obese postmenopausal women. This was a 3-months trial involving forty-nine healthy postmenopausal women with body mass index (BMI) between 25 and 35 kg/m2 who were randomly assigned to receive 3 g/d of either GSM powder (n 25) or placebo (n 24). The gut microbe abundance, serum iron status markers and body composition were measured at the baseline and the end of the study. The between-group comparison at the baseline showed a lower abundance of Bacteroides and Clostridium XIVa in the GSM group compared with the placebo (P = 0⋅04). At the baseline, the body fat (BF)% and gynoid fat% were higher in the GSM group compared with the placebo (P < 0⋅05). No significant changes were found in any of the outcome measures, except for ferritin levels that showed a significant reduction over time (time effect P = 0⋅01). Some trend was observed in bacteria including Bacteroides and Bifidobacterium which tended to increase in the GSM group while their abundance decreased or remained at their baseline level in the control group. Supplementation with GSM powder did not result in any significant changes in gut microbe abundance, body composition and iron markers compared with placebo. However, some commensal bacteria such as Bacteroides and Bifidobacteria tended to increase following supplementation with GSM powder. Overall, these findings can expand the knowledge surrounding the effects of whole GSM powder on these outcome measures in healthy postmenopausal women.
Keywords: Body composition; Greenshell mussel; Gut microbe; Iron marker; Animals; Humans; Female; Overweight; Perna; Postmenopause; Powders; Obesity; Body Composition; Microbiota; Dietary Supplements